Increasing Arm Muscle Strength and Power with Dumbbell Exercise Variations - Risfan Iskandar; Oce Wiriawan; Sapto Wibowo (Universitas Suryakancana, 2023)
The problem of this research is the lack of exercise to increase the strength and power of the arm muscles. The aim of this research is to find out whether there is an effect of dumbbell training on the strength and power of the arm muscles. The subjects of this research were 40 members of the UNDIKMA Badminton UKM. The method used in this research is quasi-experimental with a quantitative approach. Nonequivalent Control Group Design data collection. This research uses the measurement of arm muscle strength with an expanding dynamometer and arm muscle power using a two hand medicine ball put. The results of this research are that the form of exercise from groups 1, 2, and 3 has an effect on the strength and power of the arm muscles, for a greater effect, namely in group 2 with Dumbbell Bicep Curl exercises for arm muscle strength and power. Increase in strength of 11% and power of 35%. As input for this research include: 1) For UKM members this research will gain experience in weight training and know how to do the exercise, 2) For trainers it can provide insight into badminton UKM trainers regarding forms of exercise that can increase arm strength and power.Key words: Effect of Exercise, Arm Muscle Strength, Arm Muscle Power